Analisa Relay Jarak Pada Saluran Transmisi 150 Kv Pada Gardu Induk Sekarputih Ke Gardu Induk Balongbendo - Wati, Trisna; Pambudi, Wahyu Setyo; Suheta, Titiek; Warsono, Ridho Gustianto Singgih (Forum Kerjasama Pendidikan Tinggi (FKPT), 2024)
In the electric power system it does not always run normally. There are many disturbances or disturbance anomalies that can disrupt the operation of the system. One of them is at the Sekarputih main substation. last two years, the channel has experienced five short- circuit disruptions. As a result, electromagnetic distance relays must be replaced with digital distance relays equipped with reclosers. The reclosers will function when there is a relay disturbance on a trip and automatically reconnect. The disruptions may occur due to damage brought by unstable weather conditions. Indirectly, the value of relay settings will change and deviate from the PLN (state electricity company) standards. Therefore, relay re-setting was performed using two methods: the Fuzzy Mamdhani and the ANFIS methods. Using the Fuzzy Mamdhani method, the relay distance settings were as follows: Zone 1 = 0.523 Ω, Zone 2 = 0.54 Ω, and Zone 3 = 1.58 Ω. Meanwhile, the relay distance settings by the ANFIS method were: Zone 1 = 0.432 Ω, Zone 2 = 0.65 Ω, and Zone 3 = 1.22 Ω. The previous values of relay distance settings by PLN were Zone 1 = 0.587 Ω, Zone 2 = 1.046 Ω, and Zone 3 = 1.766 Ω.